2020
DOI: 10.1186/s40902-020-00264-5
|View full text |Cite
|
Sign up to set email alerts
|

Facial fractures and associated injuries in high- versus low-energy trauma: all are not created equal

Abstract: Introduction: Facial fractures (FFs) occur after high-and low-energy trauma; differences in associated injuries and outcomes have not been well articulated. Objective: To compare the epidemiology, management, and outcomes of patients suffering FFs from high-energy and low-energy mechanisms. Methods: We conducted a 6-year retrospective local trauma registry analysis of adults aged 18-55 years old that suffered a FF treated at the Santa Barbara Cottage Hospital. Fracture patterns, concomitant injuries, procedure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 10 publications
2
17
0
Order By: Relevance
“…The median length of hospital stay in our study was three days compared with 7.5 days of Mijiti et al [24]. Those with pan facial fractures and cranial injuries stay longer in the hospital [2][3][4][5]. The overall mortality in our study was 2.7% which is similar to others [5,23].…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…The median length of hospital stay in our study was three days compared with 7.5 days of Mijiti et al [24]. Those with pan facial fractures and cranial injuries stay longer in the hospital [2][3][4][5]. The overall mortality in our study was 2.7% which is similar to others [5,23].…”
Section: Discussionsupporting
confidence: 82%
“…The most commonly injured body regions associated with the face injury were the head (49.4.4%), followed by the chest (39.7%). The median (range) ISS was 5 (5-75), and the median (range) GCS was 15 (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15). Patients stayed for a median (range) of 3 (1-95) days in the hospital.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Their study differed from ours in that ground-level falls only occurred in just 14% of their cohort compared to over 40% in our study. 21 In a review of 980 patients with facial fractures in Australia, Cabalag et al reported their experience on fracture patterns and management. 5 Similar to our study, they found that approximately half of patients were treated without surgery.…”
Section: Management Trendsmentioning
confidence: 99%